Environmental risk of chlorine-controlled clogging in drip irrigation system using reclaimed water: the perspective of soil health. (20th September 2019) - Song, Peng; Feng, Gary; Brooks, John; Zhou, Bo; Zhou, Hongxu; Zhao, Zhirui; Li, Yunkai
Abstract: Chemical chlorination is an effective method to control the emitter bio-clogging in drip irrigation using reclaimed water, but the broad spectrum of strong oxidative bactericidal action of chlorine causes certain risks to soil microbial communities and even soil health. Therefore, in this study, spring maize was selected as the research object, field chlorine experiments with drip irrigation using reclaimed water were carried out in two years, high-throughput sequencing technology combined with phospholipid fatty acids (PLFAs) technology was used, the biological bio-indicator of soil health (microbial community structure of soil) in the root zone of the spring maize were systematically studied on the effects of different chlorination modes under the drip irrigation using reclaimed water. The effects of microbial community structure on soil enzyme activity and spring maize yield and quality were analyzed. The results showed that the total amount of PLFAs and bacteria content significantly decreased by 17.7 %–44.7 % and 7.0 %–47.3 %, which reduced the microbial community diversity. The relative abundance of Nitrospirae, Actinobacteria and Firmicutes decreased at the phylum level. The changes of microbial community structure reduced urease, catalase and phosphatase activities, inhibited the conversion and absorption of nutrients in the soil, which led to a decrease in crude fat and protein by 2.2 %–16.6 % and 2.2 %–14.1 %, respectively. But the yield of spring maize didn't significantly reduce. In comparison, long-term use of high concentration short duration chlorination mode was more likely to have adverse effects on soil health than low concentration long duration chlorination mode. The research results can provide a reference for the management of reclaimed water network systems and soil health. Highlights: Soil microorganism was quantified after drip irrigation using reclaimed water. The mechanism of microbial community structure changed on maize yield and quality was revealed. High concentration + short duration of chlorination was risky for soil health.